Synaptic Plasticity of Human Umbilical Cord Mesenchymal Stem Cell Differentiating into Neuron-like Cells In Vitro Induced by Edaravone - Yunpeng Shi; Chengrui Nan; Zhongjie Yan; Liqiang Liu; Jingjing Zhou; Zongmao Zhao; Depei Li (Hindawi Limited, 2018)
Objective. The human umbilical cord mesenchymal stem cells (hUMSCs) are characterized with the potential ability to differentiate to several types of cells. Edaravone has been demonstrated to prevent the hUMSCs from the oxidative damage, especially its ability in antioxidative stress. We hypothesized that Edaravone induces the hUMSCs into the neuron-like cells. Methods. The hUMSCs were obtained from the human umbilical cord tissue. The differentiation of hUMSCs was induced by Edaravone with three different doses: 0.65 mg/ml, 1.31 mg/ml, and 2.62 mg/ml. Flow cytometry was used to detect the cell markers. Protein and mRNA levels of nestin, neuron-specific enolase (NSE), and glial fibrillary acidic protein (GFAP) were detected by Western blot and RT-PCR. The expression of synaptophysin (SYN), growth-associated protein 43 (GAP43), and postsynaptic density 95 (PSD95) was detected by Real-Time PCR. Results. As long as the prolongation of the culture, the hUMSCs displayed with the long strips or long fusiform to fat and then characterized with the radial helix growth. By using flow cytometry, the cultured hUMSCs at the 3rd, 5th, and 10th passages were expressed with CD73, CD90, and CD105 but not CD11b, CD19, CD34, CD45, and HLA-DR. Most of the hUMSCs cultured with Edaravone exhibited typical nerve-immediately characters including the cell body contraction, increased refraction, and protruding one or more elongated protrusions, which were not found in the control group without addition of Edaravone. NSE, nestin, and GFAP were positive in these neuron-like cells. Edaravone dose-dependently increased expression levels of NSE, nestin, and GFAP. After replacement of maintenance fluid, neuron-like cells continued to be cultured for five days. These neuron-like cells were positive for SYN, PSD95, and GAP43. Conclusion. Edaravone can dose-dependently induce hUMSCs to differentiate into neuron-like cells that expressed the neuronal markers including NSE, nestin, and GFAP and synaptic makers such as SYN, PSD95, and GAP43.